SOCIAL MEDIA USE AND ITS IMPACT ON ADOLESCENTS’ MENTAL HEALTH AND WELL-BEING - Aleksandra Oparcik,; Jakub Tarczykowski,; Szymon Stupnicki,; Mikołaj Zakryś,; Katarzyna Anna Zakryś,; Mateusz Szot,; Natalia Kwaśniewska, (International Journal of Innovative Technologies in Social Science, 2025)
Mental health problems among adolescents have risen to unprecedented levels over the past decade. A substantial body of research has explored the relationship between social media use and adolescent well-being. The purpose of this paper is to examine research on social media use and its association with rising rates of depression, anxiety, body dissatisfaction, and suicide among adolescents. Several key themes emerge from the literature, including the negative psychological consequences of increased social media engagement, patterns of social media-related addiction, the role of fear of missing out, experiences of cybervictimization, and the influence of contagion processes. This narrative review examines articles from the PubMed, Scopus, and Google Scholar databases, with particular emphasis on recent systematic reviews, meta-analyses, and cross-sectional studies investigating how social media use affects adolescents’ mental health and well-being. While social media can provide social support, it may also amplify developmental vulnerabilities. Adolescents face a range of challenges stemming not only from the amount of time they spend on social platforms but also from the nature of the content they encounter.  Social media use has been linked to body dissatisfaction, anxiety, depressive symptoms, and elevated suicide risk. The mechanisms underlying these effects remain unclear, underscoring the need for longitudinal research examining specific online behaviors and social media platform features, such as algorithms and appearance-focused content. Future work should also explore gender-specific pathways and evaluate interventions, including digital literacy training and emotion-regulation strategies to reduce problematic social media use, and support healthier online engagement among youth.